Apple's magical iPad. - Ochs, Susie
From its brilliant screen to its smooth OS, Apple's firt-gen hardware is a hit. Plus: We score the iPad's built-in apps and pick our favorites from the iPad's App Store.
Keywords: iPad (Computer); First-generation hardware; iPad applications; iBooks; iWorks; E-reading.